Justifikasi Pemutusan Hubungan Kerja Karena Efisiensi Masa Pandemi Covid-19 Dan Relevansinya Dengan Putusan Mahkamah Konstitusi Nomor 19/PUU-IX/2011 - Dian Agung Wicaksono; Enny Nurbaningsih (Jurnal Konstitusi, 2021)
This conceptual article aims to analyze about the justification and legal aspect of employment termination because of efficiency phenomenon in covid-19 pandemic period. Article 164 paragraph 4 Manpower Act and Constitutional Court Decision Number 19/PUU-IX/2011 already stipulated that employment termination because of efficiency must be followed by company closure. But, covid-19 pandemic situation was forcing the employers to do employment termination because of efficiency without a company closure. The conclusion of this article is the employers did the termination without the company closure based on consideration that, it would prevent more damage than did it with the closure. The company closure would bring result all of workers, including the employers, loss their jobs. The employment termination because of efficiency, but without company closure could be preserved the operational of company and maintain the other workers’ jobs. This efficiency reason is not actually prohibited in Article 153 paragraph 1 Manpower Act and in ILO’s Convention and Recommendation 1982. However, this termination could not use Article 164 paragraph 4 Manpower Act and Constitutional Court Decision Number 19/PUU-IX/2011 as the legal basis. The compensation formulation model of the termination could use the formulation of termination without worker’s fault as stipulated by Manpower Act. In addition, the institutions of industrial relaton dispute resolution must supervise the termination process, in order the process would be staged fairly, coincide with the principles of legal termination, and the workers’s compensastion would be fulfilled by the employers.